Non-compliance as a determinant of constitutional change? A comparative study - Tim Schnelle (Constitutional Political Economy, 2024)
It has often been claimed that if constitutions are not complied with, they will be changed. Because an ineffective constitutional contract is a bad contract, a lack of enforcement should induce constitutional reform. This paper empirically tests this conjecture based on a dataset of 170 countries from 1950 to 2018. The results indicate that the size of the de jure/de facto gap has no effect on the likelihood of constitutional change as such. However, after differentiating between amendments and replacements as distinct modes of constitutional reform, the results imply that non-compliance robustly increases the probability of constitutional replacement only. This relationship is primarily driven by an implementation gap regarding political and civil rights. Expected moderating effects of interpersonal trust and civil society organizations as catalysts for successful civil reform movements cannot be empirically supported. Overall, this has important consequences for the writers of future constitutions. If reformers desire longevity for their new constitutional framework, they must be aware that utopian promises may backfire by provoking a quick replacement of their rules.
Keywords: H11; H73; K10; K42; O57; P48; P51; 330; Constitutional change; Constitutional compliance; De jure-de facto gap; Collective action